2020
DOI: 10.12717/dr.2020.24.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Osmolality and Acidity on Fertilized Eggs and Larvae of Olive Flounder (Paralichthys olivaceus)

Abstract: The pH of water is one of the main environmental factors exerting selective pressure on marine and freshwater organisms. Here, we focus on the influence of pH on an organism's ability to maintain homeostasis and investigate the effects of acidification on immunity-related genes and osmotic pressure during early development of the olive flounder, Paralichthys olivaceus. The aim of our study was to determine the influence of various pH levels on the fertilized eggs and larvae of P. olivaceus. Gametes of P. oliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…pH is one of the key parameters of water quality that require strict monitoring in aquaculture production because it impacts cultured animals both directly and indirectly (Fondriest Environmental Inc, 2013). It is suggested that the ideal pH range for most aquatic animals, including fish, is near neutral (Das et al, 2006;Boyd, 2013), and acute or chronic exposure to acidic water can adversely affect their physiological functions and reduce hatching, growth, and survival (Fondriest Environmental Inc, 2013;Kim et al, 2020;Prakoso et al, 2020). Meanwhile, some authors pointed out that the impacts of pH on animals usually differ between species, vary depending on a variety of specific ecological factors in the areas where they populate (Beltrão et al, 2019), and can relate to their natural history (Reynalte-Tataje et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…pH is one of the key parameters of water quality that require strict monitoring in aquaculture production because it impacts cultured animals both directly and indirectly (Fondriest Environmental Inc, 2013). It is suggested that the ideal pH range for most aquatic animals, including fish, is near neutral (Das et al, 2006;Boyd, 2013), and acute or chronic exposure to acidic water can adversely affect their physiological functions and reduce hatching, growth, and survival (Fondriest Environmental Inc, 2013;Kim et al, 2020;Prakoso et al, 2020). Meanwhile, some authors pointed out that the impacts of pH on animals usually differ between species, vary depending on a variety of specific ecological factors in the areas where they populate (Beltrão et al, 2019), and can relate to their natural history (Reynalte-Tataje et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ministry of Oceans and Fisheries of South Korea, OF aquaculture production was approximately 43,813 tons in 2020. OF is an important fish species, accounting for 65% of marine-farmed fish consumption and 50% of fish production in South Korea [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the reports of the Ministry of Ocean and Fisheries in South Korea, the olive flounder aquaculture production in 2020 was reported as 43,813 tonnes. Additionally, olive flounder accounts for 65% of marine-aquacultured fish consumption and 50% of fish production in South Korea [10]. Additionally, olive flounder has become one of the major species for surimi production in the last few years.…”
Section: Introductionmentioning
confidence: 99%